The effects of using pictograms during the English teaching-learning process in primary school - Pauzhi Coellar, Cristina (2024)
In the realm of Primary English as a Foreign Language (EFL) education, educators often encounter diverse difficulties in conveying instructions and facilitating student learning. This study recognizes the significance of employing visuals and straightforward language to enhance the teaching-learning process. Within this context, pictograms emerge as a valuable and innovative resource for EFL teachers, particularly in teaching English to children. The aim of this is to investigate the effect of pictograms on English education in primary schools. To achieve a comprehensive understanding, a slight adjustment to the class methodology was made. To operationalize this approach, a pre- and post-test, a survey, and an open-ended questionnaire were administered to collect data, facilitating a clear analysis. The first questionnaire involved three teachers who serve as heads of the English department, the survey included responses from nine primary English teachers, and the pre- and post-test garnered results from 39 primary school students. Results elucidate students’ performance, and teachers’, and heads of the English department’s perceptions of how the use of pictograms influences vocabulary acquisition, engagement, motivation, reading comprehension, and language production in English teaching and learning. By reordering the methodology and refining the ideas, the study may provide a clearer and more effective exploration of the impact of pictograms on English education in primary schools.